Towards sustainable intensification of apple production in China — Yield gaps and nutrient use efficiency in apple farming systems - Na WANG; Joost Wolf; Fu-suo ZHANG (Journal of Integrative Agriculture, 2016)
China is in a dominant position in apple production globally with both the largest apple growing area and the largest export of fresh apple fruits. However, the annual productivity of China's apple is significantly lower than that of other dominant apple producing countries. In addition, apple production is based on excessive application of chemical fertilizers and the nutrient use efficiency (especially nitrogen) is therefore low and the nutrient emissions to the environment are high. Apple production in China is considerably contributes to farmers' incomes and is important as export product. There is an urgent need to enhance apple productivity and improve nutrient use efficiencies in intensive apple production systems in the country. These can be attained by improved understanding of production potential, yield gaps, nutrient use and best management in apple orchards. To the end, priorities in research on apple production systems and required political support are described which may lead to more sustainable and environmental-friendly intensification of apple production in China.